Avaliação da atividade antiviral de compostos triterpênicos contra o Vírus Sincicial Respiratório - Atik, Diana Monti (2016)
Respiratory Syncytial Virus (RSV) is an enveloped RNA virus of the lipid bilayer that originates from the host cell and belongs to the Paramyxoviridae family. RSV causes acute respiratory tract infection and is the leading cause of hospitalization and death among children under 5 years worldwide. Currently there is no licensed vaccine available on the market. Thus, a need exists for the development of antiviral therapeutics. The triterpenoid compounds, including, betulinic acid, ursolic acid and betulin have a variety of pharmacological and biological activities, including antiviral activity. In this study, we tested compounds derived from betulinic acid, ursolic acid and betulin as its cytotoxicity and antiviral activity. The LAFIS131 and LAFIS134 compounds had significant antiviral activity in vitro protecting cells from death caused by RSV. These compounds showed an index of selectivity of 2:09 and 25.5, respectively, indicating that the LAFIS134 would be the most promising compound because besides having antiviral activity, non-cytotoxic, making it more selective for cells infected with RSV.